Moving to local control of woodland resources - Can CAMPFIRE go beyond the mega-fauna? - Campbell, Bruce M.; Byron, R.N.; Madzudzo, Pauline H.E.; Matose, F.; Wily, L. (1999)
Devolution of authority over natural resource management is now well advanced for the mega-fauna in Zimbabwe, through the CAMPFIRE program. We ask whether models like CAMPFIRE can be applied to a broader spectrum of woodland resources. Problems in applying CAMPFIRE to woodland resources relate to a legal and policy framework that is not enabling to local management; weakened local institutional structures; a high of differentiation with respect to woodland resource use within communities; problems of defining resource user groups; and, the potentially low market value of woodland products. In identifying circumtances where CAMPFIRE may be applied succesfully to woodland resources, economic, sociological, and ecological circumtances must be considered.